On the present state of the law and practice in Ireland with respect to wills and the administration of assets - Lawson, James A. (Social Inquiry Society of Ireland, 1852)
I beg leave to submit to you the following report upon the question proposed to me for investigation; namely, 'The Present State of the Law and Practice in Ireland with respect to Wills, with a view to have all wills proved and registered at the domicile of the deceased, and to have the jurisdiction with respect to legacies, devises, the administration of assets, and the validity of wills consolidated and vested in the same Court.' Following the course naturally suggested by the question itself, I propose to point out the present state of the law and its practical working in this country, upon the following points:? 1. The proof of wills. 2. The registry of wills. 3. The custody of wills. 4. The decision of questions respecting the validity of wills. 5. The decision of questions arising upon the construction ot wills. 6. The administration of assets. I propose to notice, as I proceed, the defects in the present system, under each of the foregoing heads. And in the last place, I propose to suggest such alterations in the law as appear to me necessary in order to remove those defects, and introduce a better system.
Delivery date of paper not given
Keywords: Ireland; Law; Estates Law; Wills; 314.15